Difference of natural teeth and implant-supported restoration: A comparison of bone remodeling simulations - Chao Wang; Gang Fu; Feng Deng (Elsevier, 2015)
Background/purpose: Although there are existing numerical simulation studies on biomechanical responses induced by dental implants, particular attention has not been paid to the discrepancies of alveolar bone around natural teeth and dental implants. The purpose of this study was to compare and assess the different consequences of alveolar bone remodeling before and after dental implantation. Materials and methods: Two three-dimensional finite element (FE) models of a maxillary bone segment were developed, comprising either implant-supported dental bridgework or natural teeth. A set of three-dimensional orthotropic bone remodeling algorithms was implemented in the FE models to analyze the stress, strain, and density distribution in the supporting bone. Results: There were significant differences in the stress, strain, and density distribution between the intact model and implanted model. The variation of stress value was remarkably different in both models, and evident differences were found in the high stress region. Strain value was elevated in cortical bone around the implant neck, but in the intact bone strain value was distributed more evenly. In addition, bone density distribution around natural teeth was more uniform and homogeneous. Conclusion: Simulations of adaptive bone remodeling, validated by clinical data, can be proved as a useful way to bring more insight into the mechanisms behind bone adaptation. In consideration of the crucial role of the periodontal ligament (PDL) in determining the mechanical environment in alveolar bone, it is suggested that the effect of the PDL on the bone remodeling response should be considered in future dental implant design.